The influence of Accounting Information Quality on Investment Decisions: Investor Perspective in the Capital Market - Putu Saroyini Piartrini; PA Andiena Nindya Putri (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This article delves into the critical role of accounting information quality in shaping investment decisions from the perspective of investors in the capital market. The research aims to explore how the quality of accounting information impacts the decision-making processes of investors, particularly in terms of assessing investment opportunities and managing risks. A comprehensive literature review is conducted to analyze previous studies and theories related to accounting information quality, investment decisions, and investor behavior. The findings suggest that high-quality accounting information positively influences investors' ability to evaluate investment options accurately, enhances transparency, reduces information asymmetry, and fosters confidence in financial markets. Conversely, poor-quality accounting information can lead to misinformed decisions, increased uncertainty, and potential financial losses for investors. The implications of these findings highlight the significance of reliable and transparent financial reporting practices in facilitating informed investment decisions and promoting efficiency in capital markets.